Evaluación de severidad en la mancha de asfalto (Phyllachora maydis) en el cultivo de maíz (Zea mays) bajo el efecto del óxido de silicio (SiO2) - Vinces Tachong, Romulo Enrique (2021)
The cultivation of corn (Zea mays) is important in Ecuador due to the role it plays in feeding the population. This is affected by different diseases of fungal origin and by pests such as the asphalt stain fungus (Phyllachora maydis). Silicon is the fifth element that presents great accumulation in plant tissues, which is why it is considered a trace element. The present investigation carried out in the facilities of the Campus "La María" of the State Technical University of Quevedo, located at Km 7 via Quevedo, had the objective of evaluating the control of the severity of the asphalt stain using silicon oxide in the crop. of corn. For the experimental design of the research, randomized complete blocks (BCA) were used. The information was processed in the statistical program Infostat and each evaluated treatment was subjected to ANOVA tests and Tukey's multiple range tests with a significance level of 0.05%. Data on the severity of the asphalt stain were collected using visual assessment scales and the Leaf Doctor image processor. An economic analysis of the application was performed for profitability based on production costs. As a result, it was determined which Leaf Doctor program can be used to evaluate the asphalt stain. When analyzing the degree of severity by Class 0 (Sev. 0%), Class 1 (Sev. 1-6%), Class 2 (Sev. 7-22%), Class 3 (Sev. 56-84%), Class 4 (Sev. 85-95%) and Class 5 (Sev. 96-100%). In the low leaves that are more prone to getting sick, presenting a damage of 4.47% in the program and 4.90 in the visual analysis by means of the pathogen. Finally, the silicon dose of 168kg / ha presented resistance to the disease and higher profitability with $ 1004 which is equivalent to a (50% profitability) in relation to the control. Keywords: silicon, tar spot, corn.